2010
DOI: 10.1039/c000863j
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous fabrication of arrays of normally closed, adjustable, and reversible nanochannels by tunnel cracking

Abstract: A direct fabrication method capable of producing fully-reversible, tunable nanochannel arrays, without the use of a molding step, is described. It is based on tunnel cracking of a readily-prepared brittle layer constrained between elastomeric substrates. The resulting nanochannels have adjustable cross-sections that can be reversibly opened, closed, widened and narrowed merely by applying and removing tensile strains to the substrate. This permits reversible trapping and release of nanoparticles, and easy prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 26 publications
0
61
0
Order By: Relevance
“…We recently showed that the spring constant of channel-confined DNA depends in a non-trivial way on the aspect ratio of the channel [100], and it is reasonable to assume that hydrodynamic interactions may also exhibit similarly peculiar behavior. It would also be worthwhile to consider other ways that the channel shape can affect the hydrodynamic interactions, either using circular channels to eliminate the corner flows or using triangular channels [123,124] to enhance the importance of these flows. Such simulations for circular confinement are driven more by curiosity, since fabrication of transparent circular nanochannels suitable for fluorescence microscopy is challenging but possible [125].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that the spring constant of channel-confined DNA depends in a non-trivial way on the aspect ratio of the channel [100], and it is reasonable to assume that hydrodynamic interactions may also exhibit similarly peculiar behavior. It would also be worthwhile to consider other ways that the channel shape can affect the hydrodynamic interactions, either using circular channels to eliminate the corner flows or using triangular channels [123,124] to enhance the importance of these flows. Such simulations for circular confinement are driven more by curiosity, since fabrication of transparent circular nanochannels suitable for fluorescence microscopy is challenging but possible [125].…”
Section: Discussionmentioning
confidence: 99%
“…Such simulations for circular confinement are driven more by curiosity, since fabrication of transparent circular nanochannels suitable for fluorescence microscopy is challenging but possible [125]. In contrast, triangular channels are easily fabricated [123,124] and provide a stronger extension than a square channel for a given cross-sectional area [126,127]. Moreover, hydrodynamic interactions may play a crucial role for the strong stretching found in “normally closed” triangular nanochannels [124].…”
Section: Discussionmentioning
confidence: 99%
“…Consider a thin slice of the cylinder of length dL, opening under plane-displacement conditions. 1 The problem can be analyzed by superposition of the solutions to two problems: (i) plane-strain deformation under exterior radial tractions and (ii) This is the assumption that plane sections perpendicular to the axis of the channel remain plane, and is enforced with the additional constraint of no net axial load. It is this second requirement that distinguishes plane-displacement boundary conditions from plane-strain conditions.…”
Section: Axisymmetric Tubesmentioning
confidence: 99%
“…Scanning-electron microscopy and laser confocalmicroscopy have been used to characterize surface cracks [1,4,10]. The results provide some reference for the shape and size of tunneling cracks, but do not reflect the real profiles of liquid-filled nanochannels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation